ITEMAN-Based Evaluation of End-of-Semester Assessment Items: A Case Study of Language Test in Indonesian School Context - Riswanda Himawan; Hermanto Hermanto; Burhan Nurgiyantoro; Suyono Suyono; Didin Widyartono; Agustina Purwanti; Le Yujing; Victor A. Pogadaev (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
Assessment is an inseparable part of the learning process. Assessment is a way to decide the choices that a teacher will make for students, so that what they do is truly measurable. In line with this description, this study aims to determine the quality of the end-of-semester assessment questions for Indonesian, grade VIII, at SMPN 8 Yogyakarta. The method used in this research is descriptive quantitative. Quantitative descriptive is used to analyze documents in the form of output analysis results from the ITEMAN application. The results of the review that will be submitted later are in the form of validity, reliability, IDB, ITK and the functioning of the distractor. In obtaining the results of the study. The research steps carried out in this study were are testing the validity of the question grids, testing the reliability, IDB, ITK, and distractors through the ITEMAN program, analyze the results according to expert opinions and research that are relevant to this study, and conclude the results of the study. There were 50 questions that were analyzed and tested on 32 class VIII students of SMPN 8 Yogyakarta. Overall, the research results show all questions are declared valid, Alpha is 0.926. This shows that the reliability of the items is very high, IDB results show 38 items in good, 5 moderate, 4 sufficient, and 3 failed categories, the results of ITK analysis showed 31 very easy questions, 10 easy questions, 5 moderate questions, 2 difficult questions, and 2 very difficult questions, and the results of the distractor function show that 32 questions do not work, and 18 item distractors work. Overall, the results of this analysis aim to provide a reference base related to the quality of questions through ITEMAN, especially in learning Indonesian, which so far has not been done much.